Factores epidemiológicos de la hipercalcemia en pacientes adulto - Yaguana Chávez, Miguel Roberto (Machala : Universidad Técnica de Machala, 2019)
INTRODUCTION: Hypercalcemia is defined as the concentration of serum calcium greater than 8.8-10.2 mg / dL. It occurs in 0.05-0.6% of the general population and 0.6-3.6% of hospitalized patients. It is a finding in people who attend primary care, emergency and patients admitted to the hospital. OBJECTIVE: To establish the epidemiological factors of hypercalcemia in adult patients. METHODOLOGY: For the collection of scientific information, search articles articles in databases such as COCRHANE, PUB-MED, LATINDEX, published since 2014, in indexed journals. CONCLUSIONS: The main causal factor of hypercalcemia is parathyroid hormone in 80% of cases, cancer follow-up and thyroid surgery; Vitamin D poisoning is rare. 81.8% of patients with hypercalcemia do not present symptoms while 18.2% are symptomatic. The total incidence of hypercalcemia related to cancer is 6.95 per year.
INTRODUCCION: La Hipercalcemia es definida como la concentración del calcio sérico mayor a 8,8-10,2 mg/dl. Se presenta en el 0,05-0,6% de la población general y el 0,6-3,6% de los pacientes hospitalizados. Es un hallazgo en personas que acuden a atención primaria, emergencia y en pacientes ingresados en el hospital. OBJETIVO: Establecer Los factores epidemiológicos de la Hipercalcemia en pacientes adultos METODOLOGIA: Para la recopilación de información científica, se buscaron artículos científicos en bases de datos como COCRHANE, PUB-MED, LATINDEX, publicados desde el año 2014, en revistas indexadas. CONCLUSIONES: El principal factor causal de la Hipercalcemia es la hormona paratiroidea en un 80% de los casos, seguido por el cáncer y cirugía de tiroides; la intoxicación por vitamina D, es rara. El 81.8% de pacientes con hipercalcemia no presentan sintomatología mientras que18.2% es sintomático. La incidencia total de Hipercalcemia relacionada con Cáncer es de 6.95 por año.
Keywords: HIPERCALCEMIA; EPIDEMIOLOGIA; HIPERCALCEMIA; MANEJO HIPERCALCEMIA